A fresh look at writing - Graves, Donald H. (Portsmouth, N.H. Heinemann, 1994)
Describes techniques that teachers can use to increase their students' appreciation for writing and offers a detailed, week-by-week description of fourteen sessions designed to improve students' writing and reading skills.
I. Make a fresh start -- 1. Consider your roots -- 2. Learn from the children -- 3. Why would anyone ever want to write? -- 4. Day one : help children to write and keep writing -- 5. Understand Children When They Write -- 6. Expect More of Your Writers -- II. Establish the Essentials for Child Responsibility -- 7. Conditions for Effective Writing -- 8. Begin to Organize Your Classroom -- 9. Help Children to Share Their Writing -- 10. Evaluate Your Own Classroom -- 11. Experiment with Portfolios -- III. Teach the Fundamentals of Writing -- 12. Help Children Learn Conventions -- 13. Help Children to Read Their Own Work -- 14. Help Children to Revise Their Work -- 15. How to Keep Handwriting in Perspective -- 16. Spell to Communicate -- 17. Answers to Frequent Questions Teachers Ask About Teaching Writing -- IV. Broaden the Children's Repertoire for Writing -- 18. Help Children Read and Write Fiction -- 19. Show Children How to Write Nonfiction -- 20. Uncover the World Through Poetry.
Keywords: English language -- Composition and exercises -- Study and teaching (Elementary); Creative writing (Elementary education)